MODAL SOSIAL DAN PENGEMBANGAN PENDIDIKAN KEPENDUDUKAN JALUR PENDIDIKAN INFORMAL - Muhammad Ancha Sitorus; Evalina Franciska Hutasoit (Duconomics Sci-meet (Education & Economics Science Meet), 2021)
One of the main assets in development is a quality population. In improving the quality of the population, the development must be adjusted to the needs of the environment and the dynamics of community development with regarding the various potentials, current conditions, and problems in the community. The number of children and community dropping out of school are unable to complete a formal education is a problem, especially during the COVID-19 pandemic. Dropouts are closely related to population and social problems such as increasing cases of child marriage, poverty, and unemployment. The integration of population education in the informal education pathway is an alternative to build the public awareness and the independence that reaches the community, especially vulnerable groups of people. The development of the community can’t be separated from the support of social capital by involving all parties, including in informal education. Social capital builds communities to become more responsible for preparing and developing programs. Agreement strengthening and social mapping are the main key with the involvement of various parties to participate in increasing community participation in informal education. Population education is integrated with informal education which is built in a curriculum with material based on the issue of local wisdom that is arranged for building awareness and be able to survive during the COVID-19 pandemic. Through this activity, it is hoped that this activity will be able to increase participation and development constructive that strengthens the spirit of mutual cooperation in building self-reliance in community to be able to survive during the COVID-19 pandemic, especially the event of dropping out of school to return to study in formal or non-formal education as compulsory education for every member of the community